Question #fa20c

1 Answer
Feb 24, 2018

See below.

Explanation:

The identities

I_1->a (x - 1)^2 + b (2 x - 1) (x - 1) + c (x + 3) equiv (5 - x)I1a(x1)2+b(2x1)(x1)+c(x+3)(5x)

I_2->a (x - 2)^2 + b (x - 1)^2 + c equiv (3 x^2 - 8)I2a(x2)2+b(x1)2+c(3x28)

are obtained after expanding and grouping coefficients given

I_1->{(a+b+3c=5),(2a+3b=1),(a+2b=0):}

and solving we obtain a=4,b=-2,c=1

so

I_1->4 (x - 1)^2 -2 (2 x - 1) (x - 1) + (x + 3) equiv (5 - x)

analogously we have

I_2->-3 (x - 2)^2 +6 (x - 1)^2 -2 equiv (3 x^2 - 8)